Tantangan Pemanfaatan Teknologi Era 4.0 di Lingkungan Remaja Mesjid Jabal Nur SPN Padang Besi - Tasnim, M.; Maulana, Ilham Tri; Edison, Elisa Daniati; Rahmelina, Liranti; Juwita, Arika (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
Efforts made in preparing quality students, especially in developing technological science, understand in advance the challenges faced in the use of technology used today. Knowledge of the real challenges for educators in choosing the best technological tools, so that educators do not lose their teaching goals, and do not misunderstand students. This activity is proof of the seriousness of the Jabal Nur SPN Padang Besi Teenagers in realizing their commitment to quality Youth. Therefore this PkM teaches students to understand the challenges of using technology in the 4.0 era. This activity needs a modules related to the challenges of using technology in the 4.0 era, and enrichment from quizzes online adapted to the PkM material. The activity phase that has been carried out in this community service activity is to provide integrated training so that teenagers at the Jabal Nur SPN Padang Besi Mosque can understand, understand and prepare and improve quality in the challenges of using technology in Era 4.0. The results of this service students take tests and find out the results of tests carried out through quizzes online. The next plan is to assign tasks and evaluate the tasks that have been given by the implementing team